The role of GSK-3 in synaptic plasticity - Peineau, S (Nature Publishing Group, 2008)
Glycogen synthase kinase-3 (GSK-3), an important component of the glycogen metabolism pathway, is highly expressed in the CNS. It has been implicated in major neurological disorders including Alzheimer's disease, schizophrenia and bipolar disorders. Despite its central role in these conditions it was not known until recently whether GSK-3 has neuronal-specific functions under normal conditions. However recent work has shown that GSK-3 is involved in the regulation of, and cross-talk between, two major forms of synaptic plasticity, N-methyl-D-aspartate receptor (NMDAR)-dependent long-term potentiation (LTP) and NMDAR-dependent long-term depression (LTD). The present article summarizes this recent work and discusses its potential relevance to the treatment of neurological disorders.